2019
DOI: 10.1038/s41467-019-11799-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-relapse neurons in the infralimbic cortex of rats drive relapse-suppression by drug omission cues

Abstract: Drug addiction is a chronic relapsing disorder of compulsive drug use. Studies of the neurobehavioral factors that promote drug relapse have yet to produce an effective treatment. Here we take a different approach and examine the factors that suppress—rather than promote—relapse. Adapting Pavlovian procedures to suppress operant drug response, we determined the anti-relapse action of environmental cues that signal drug omission (unavailability) in rats. Under laboratory conditions linked to compulsive drug use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 78 publications
(142 reference statements)
3
10
0
Order By: Relevance
“…This suggests that the IL cortex can also function as a driver of heroin seeking, consistent with other reports 5 7 . Nonetheless, our findings in this heroin model are consistent with observations that IL neuronal ensembles exert inhibitory control over alcohol seeking 41 , 42 . As specific IL outputs were not identified in the latter studies, these apparent discrepancies may relate to different IL outputs being engaged under different conditions.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that the IL cortex can also function as a driver of heroin seeking, consistent with other reports 5 7 . Nonetheless, our findings in this heroin model are consistent with observations that IL neuronal ensembles exert inhibitory control over alcohol seeking 41 , 42 . As specific IL outputs were not identified in the latter studies, these apparent discrepancies may relate to different IL outputs being engaged under different conditions.…”
Section: Discussionsupporting
confidence: 91%
“…The present results also mirror findings showing distinct roles of neuronal ensembles in mediating diverse behaviors. We and others found that different neuronal ensembles in the vmPFC mediate self‐administration versus extinction of food and cocaine seeking 23,26,27 . In a separate study, we found that neuronal ensembles in dorsomedial striatum are critical for methamphetamine seeking but not food seeking 19 .…”
Section: Discussionsupporting
confidence: 51%
“…Until relatively recently, the tools required to test the role of neuronal ensembles in drug‐seeking have not been available. Recent reports indicate that neuronal ensembles are critical for conditioned responses and relapse to several drugs, including cocaine, heroin, alcohol, nicotine, and methamphetamine 18–26 . In a previous studies, we found that neuronal ensembles within ventral mPFC are critical for both cocaine and food seeking 24,27 .…”
Section: Introductionmentioning
confidence: 46%
“…Our findings here suggest that simply reducing activity in the OFC shallow layers is not sufficient to reduce sucrose seeking and highlight how Fos levels are not necessarily influenced by changes in behavioral output on test day. Mounting evidence from our group and others demonstrate that distinct, sparse sets of activated neurons or “neuronal ensembles” in the prefrontal cortex mediate cue‐evoked reward seeking for food and drug rewards (Laque et al., 2019; Suto et al., 2016; Warren et al., 2016, 2019; Whitaker et al., 2017). These findings raise the possibility that while long exposure to EE may reduce activity in the OFC more generally, it may not necessarily do so in neuronal ensembles which subserves conditioned approach responses.…”
Section: Discussionmentioning
confidence: 97%